(untitled) - Milliken, Marian D. (Paramus, NJ, 2001)
This unique information source and time-saver for new and experienced physical education teachers provides over 250 handy lists related to the P.E. program and curriculum that can be reproduced for student use or kept on hand as a reference in planning sports, games, and activities.The lists cover all aspects of the physical education teacher's work, including program goals and objectives; adapted physical education; game rules and facts; fitness and metric conversion charts; height and weight charts; athletic equipment; national P.E. organizations with web sites; and field, court, or playing area diagrams. For quick access and easy use, the lists are organized into three sections covering (1) goals, (2) games, and (3) guides, numbered consecutively throughout, and printed in a big 8 1/2" x 11" lay-flat format for easy photocopying of any list as many times as needed.
Keywords: Physical education and training,Sports,Giáo dục và đào tạo thể chất,Thể thao